Numerical modeling of flow stress and grain evolution of an Mg AZ31B alloy based on hot compression tests - Giorjao, R. A.R.; Monlevade, E. F.; Avila, J. A. [UNESP]; Tschiptschin, A. P. (Springer Nature, 2020)
Magnesium alloys offer a wide range of applications in modern lightweight structures, although the correct forming parameters need to be found to reach a good combination of fine microstructure and the required mechanical properties. Several discrete and statistical methods have been proposed to simulate the dynamic recrystallization process and adopted to study microstructural evolution. However, the materials parameters necessary to develop these models are not widely available. Hence, industrial evaluation of these parameters is complex, unpractical for several types of material and time consuming for daily industrial applications. In that way, the thermomechanical behavior and grain size evolution modeling of the AZ31 alloy are proposed using isothermal compression data. Parameters to calculate coupled stress–strain–temperature parameters, dynamic recrystallization, volume fraction and grain size were obtained from the stress–strain curves. Then, the data were input in Deform-3D software to simulate the hot deformation process and verify with experimental data the consistency of the values obtained. Measured grains size agreed with the conducted modeling, showing the reliability of strain–stress and grain size data on predicting dynamic recrystallization phenomena.
Keywords: AZ31B; Dynamic recrystallization; Finite element modeling; Gleeble simulation; Isothermal compression